Progressive method of welding irreversible joints of steel pipes of winter greenhouse heating systems - CHEPURNYI, Volodymyr; CHEPURNA, Nataliia (Ways to Improve Construction Efficiency, 2025)
The article presents design and technological solutions for heating systems in winter greenhouses. It describes the total labour costs of installing heating systems during the construction of greenhouse complexes. An analysis of the use of traditional methods of welding steel pipes is carried out, and the positive and negative aspects of their use are identified. The technological features and welding modes of traditional methods of connecting pipes in greenhouse heating systems are presented. Data on the main necessary welding materials and equipment are provided. High material consumption and labour intensity, low productivity and the dependence of the quality of welding work on the level of qualification of the performers are noted, which affects the long-term safe operation of greenhouse heating systems. The issue of reducing the construction time of greenhouse complexes by introducing a progressive method of welding steel pipes during welding and installation works on greenhouse heating systems is considered. The use of automatic pipe welding with a magnetically controlled arc is recommended. Scientists at the E.O. Paton Electric Welding Institute (Kyiv) are engaged in the development of this technology and welding equipment. Samples of developed welding installations are presented and the essence and technical indicators of the process of automatic magnetically controlled arc welding of steel pipes are described in detail. The technological aspects of ensuring the quality of welded joints during automatic magnetically controlled arc welding and the technological features of the welding mode for joints of greenhouse heating system pipes are considered. Magnetically controlled arc welding technology has great potential for modernising the welding of steel pipes, offering high efficiency, quality and cost-effectiveness compared to traditional welding methods. The creation of mobile welding complexes based on welding equipment and their introduction into the construction of greenhouse complexes allows for improving the quality of welding and installation work, reducing the time required to commission greenhouse heating systems, as well as the rational use of labour and savings in material costs. The trends and directions for the further implementation of modern domestic welding equipment and progressive technologies for welding pipe heating systems in the construction of greenhouses and greenhouse complexes are described.